Flora & Ulysses [compact disc, unabridged] : the illuminated adventures - DiCamillo, Kate (Listening Library, 2013)
"She is a natural-born cynic! He is an unassuming squirrel! Together, Fora & Ulysses will conquer villains, defend the defenseless, and protect the weak, or something"--Container.